Thermal Analysis of Permanent Magnet Direct Drive Synchronous Traction Motor for Metro Vehicles - Xionghui HU (机车电传动)
With the development of permanent magnet traction system, the requirements of high power density and high torque density are put forward for the motor. Thermal analysis becomes more and more important in the design process of the motor. Taking a permanent magnet direct drive synchronous traction motor for a metro vehicle as an example, based on the design method of thermal analysis, the main considerations in the design process, the choice of cooling mode, and the key parameters of the design of water-cooled frame were put forward, and the three-dimensional simulation results and test data were compared. The comparison results showed that the simulation value of stator temperature was in good agreement with the test data. The proposed design method could provide reference for the design engineer of permanent magnet direct drive synchronous traction motor.